Effects of macro vs. micro initialization and ocean initial-condition memory on the evolution of ensemble spread in the CESM2 large ensemble - Clara Deser; Who M. Kim; Robert C. J. Wills; Isla R. Simpson; Steve Yeager; Gokhan Danabasoglu; Keith Rodgers; Nan Rosenbloom (Climate Dynamics, 2025)
“Single Model initial-condition Large Ensembles” (SMILEs) conducted with Earth system models have transformed our ability to quantify internal climate variability and forced climate change at local and regional scales. An important consideration in their experimental design is the choice of initialization procedure as this influences the duration of initial-condition memory, with implications for interpreting the temporal evolution of both the ensemble-mean and ensemble-spread. Here we leverage the strategic design of the 100-member Community Earth System Model version 2 (CESM2) SMILE to investigate the dependence of ensemble spread on the method of initialization (micro- vs. macro- perturbations) and the effects of ocean initial-condition memory. We find that the evolution of ensemble spread in 10-year low-pass filtered data is relatively insensitive to the method of initialization beyond the second decade, with the notable exception of the tropical Indo-Pacific in the 4th decade, when macro-initialization significantly enhances ensemble spread, possibly as a result of a state-dependent response to major volcanic activity. Initial-condition memory associated with the chosen Atlantic Meridional Overturning Circulation (AMOC) states unfolds in two stages: First, in the North Atlantic lasting 4–5 decades, and subsequently, in the Indo-Pacific sector of the Southern Ocean appearing 35-years after initialization and lasting 3–4 decades. Known AMOC dynamics explain the first stage, but the role of AMOC and the mechanisms responsible for the delayed appearance of initial-condition memory in the Southern Ocean remain to be fully elucidated. Implications and recommendations for the design of future SMILEs are provided.

An evaluation of the seasonal Caribbean hydroclimate in low and high-resolution CESM and other CMIP6 models - Carlos J. Martinez; Isla R. Simpson; John T. Fasullo; Andreas F. Prein (Climate Dynamics, 2025)

Recent and near‐term future changes in impacts‐relevant seasonal hydroclimate in the world's Mediterranean climate regions - Richard Seager; Yutian Wu; Annalisa Cherchi; Isla R. Simpson; Timothy J. Osborn; Yochanan Kushnir; Jelena Lukovic; Haibo Liu; Jennifer Nakamura (International Journal of Climatology, 2024)
Change over recent decades in the world's five Mediterranean Climate Regions (MCRs) of quantities of relevance to water resources, ecosystems and fire are examined for all seasons and placed in the context of changes in large‐scale circulation. Near‐term future projections are also presented. It is concluded that, based upon agreement between observational data sets and modelling frameworks, there is strong evidence of radiatively‐driven drying of the Chilean MCR in all seasons and southwest Australia in winter. Observed drying trends in California in fall, southwest southern Africa in fall, the Pacific Northwest in summer and the Mediterranean in summer agree with radiatively‐forced models but are not reproduced in a model that also includes historical sea surface temperature (SST) forcing, raising doubt about the human‐origin of these trends. Observed drying in the Mediterranean in winter is stronger than can be accounted for by radiative forcing alone and is also outside the range of the SST‐forced ensemble. It is shown that near surface vapour pressure deficit (VPD) is increasing almost everywhere but that, surprisingly, this is contributed to in the Southern Hemisphere subtropics to mid‐latitudes by a decline in low‐level specific humidity. The Southern Hemisphere drying, in terms of precipitation and specific humidity, is related to a poleward shift and strengthening of the westerlies with eddy‐driven subsidence on the equatorward side. Model projections indicate continued drying of Southern Hemisphere MCRs in winter and spring, despite ozone recovery and year‐round drying in the Mediterranean. Projections for the North American MCR are uncertain, with a large contribution from internal variability, with the exception of drying in the Pacific Northwest in summer. Overall the results indicate continued aridification of MCRs other than in North America with important implications for water resources, agriculture and ecosystems.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.